Layanan Informatif Penggunaan Media Poster Dalam Layanan Bimbingan Klasikal Untuk Peningkatan Pemahaman Kekerasan Gender Berbasis Online (Kgbo) Pada Siswa Kelas X Sma Kemala Bhayangkari 1 Kubu Raya - Dea Dwenta Septiani; Hesty Nur Rahmi; Bella Yugi Fazny (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
This study aims to determine the effectiveness of informative services in improving students’ understanding of Online Gender-Based Violence through posters and lectures. A quantitative approach was applied using a quasi-experimental design of the pretest-posttest non-equivalent control group type. The subjects were tenth-grade students of SMA Kemala Bhayangkari 1 Kubu Raya, with class X B as the experimental group and class X E as the control group. Data analysis techniques included percentage analysis to measure improvement, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank test due to non-normal data. The results showed significant improvement in both groups, with posttest scores reaching 379 (85%) in the experimental group and 213 (47%) in the control group, both with a significance value of 0.000.